SHIRIN MAKKАJO‘ХORINING AGROSANOATGA QO‘SHGAN HISSASI VA YAKKABOG‘ SHAROITIDA UNING SUV TALABI HAMDA EVAPOTRANSPIRATSIYA KO‘RSATKICHLARI (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article scientifically analyzes the role of sweet corn in the agro-industrial complex, its processing potential, contribution to food security, as well as the water demand and evapotranspiration (ET) indicators of this crop in the conditions of the Yakkabog district. Although practical experiments on the crop have not yet been conducted, using agro-climatic indicators, scientific sources, and modeling methods, scientific proposals have been developed on the water consumption of sweet corn, periodic changes in EC, the level of provision with available water resources, and the optimal irrigation regime.